8-9 YEAR OLD CHILDREN EMPATHY AND EMOTIONAL REGULATION MEASURMENT CHANGES IN NON - VIOLENT COMMUNICATION INTERVENCE PROGRAM BY M. ROSENBERG - Ozola, Laura; Plaude, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of this paper is to investigate the 2nd grade children empathy and emotional regulation differences, after non – violent communication intervence program. Non- violent communication intervence program is based on M.Rosenberg,(2003) four step model. Nowdays a lot of schools and teachers, have a huge problem to deal with children challenging behaviour, like antisocial and impulsive, bulling, verbal, non verbal agression, conflicts and the latest researches have shown, that it is strictly connected with social – emotional competence problems. First of all, emotional regulation influences peer relationship quality and life’s well being and success maintenance (Lane, 2000). Although, empathy is one of the most essential social competences components and has a strong connection between ourselves and others and is the biggest motivator of prosocial behaviour (de Waal, 2008). Zin & Elias state, that practicing different intervence programms based on social, emotional and mindfulness exercises with the focus on thoughts, feelings, meditation is the direct way to enlarge empathy and emotional regulation (Zin & Elias,2007).